Synthesis, Characterization and Study Thermal Stability of New Polythiadizole Derivatives / Silica Nanocomposites - Maha T. Sultan (Journal of Global Pharma Technology, 2019)
New nanocomposites containing polythiadizole were synthesized by free radical polymerization and examined their thermal properties. All monomers, polymers and nanocomposites were characterized by FT-IR spectroscopy. The thermal stability were investigated by thermo gravimetric (TG), differential scanning calorimetry (DSC) and differential thermal analysis (DTA). Synthesis of polymer and their nanocomposite had characterization by FT-IR, thermogravimetry (TG), Diffraction scanning callomatry DSC, Differential Thermal analysis DTA,the state of the nanocomposite were evaluated via X-ray diffraction (XRD).The results of thermal analysis showed that nanocomposite more stable than their polymers. Keywords: Thermal stability, Polymers, Thiadiazole, Nano composite.